Методика прогнозирования последствий низовых лесных пожаров - Dmitrichenko Александр; Vrublevskiy Андрей (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2011)
The methods of ground fires consequences prognostication has been elaborated basing on the Rotermel mathematical model. The elaborated methods have the advantage of using only those input parameters which can be determined beforehand without carrying out natural fire testing. That stipulates the practical significance of the elaborated methods.